The Values of Tawakkal and Husnuzan toward Allah in the Lyrics of the Song Insya Allah by Maher Zain - Amara Putri Pertiwi; Andini Khairunisa Sulaiman; Laela Tusaadah; Tsulis khoerunnisa Amanah; Dadan Firdaus (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This article examines the values of tawakkal and husnuzan toward Allah contained in the lyrics of the song Insya Allah by Maher Zain. This study is motivated by the absence of research that specifically analyzes the song using the framework of Akhlak Tasawuf, particularly the theory of tawakkal according to Al-Ghazali in Ihya’ Ulumuddin and the theory of husnuzan according to Ibn Qayyim al-Jauziyyah in Madarij al-Salikin. The study employs a qualitative approach with content analysis and library research as its method. The data consist of linguistic units in the lyrics, which are analyzed using the Miles and Huberman interactive model through three stages: data reduction, data display, and conclusion drawing, with data validity ensured through theoretical triangulation. The analysis shows that the lyrics of Insya Allah contain the value of tawakkal, which encompasses Al-Ghazali’s three levels, ranging from expressions of surrender to Allah, calls not to despair, to total submission in seeking guidance. The value of husnuzan appears dominantly through the phrase “Insya Allah there’s a way,” repeated eight times, the belief in Allah’s presence and nearness, and the pattern of active effort that demonstrates husnuzan in this song belongs to the mahmud (praiseworthy) category according to Ibn Qayyim al-Jauziyyah’s classification, not ghurur. This study is expected to fill the gap in previous research while also showing that the values of Akhlak Tasawuf can be experienced through contemporary musical works.